The party line : how the media dictates public opinion in modern China - Young, Doug (Professor, Fudan University Journalism School) (Wiley, 2013)
"The first in depth, authoritative discussion of the role of the press in China and the way the Chinese government uses the media to shape public opinion. China's 1.3 billion population may make the country the world's largest, but the vast majority of Chinese share remarkably similar views on these and a wide array of other issues, thanks to the unified message they get from tightly controlled state run media. Official views are formed at the top in organisations like the Xinhua News Agency and China Central Television and allowed to trickle down to regional and local media, giving the appearance of many voices with a single message that is reinforced at every level. As a result, the Chinese are remarkably like minded on a wide range of issues both domestic and foreign. Takes readers beyond China's economic miracle to show how the nation's massive state run media complex not only influences public opinion but creates it. Explores an array of issues, from Tibet and Taiwan to the environment and US trade relations, as seen through the lens of the Xinhua News Agency. Tells the story of the official Xinhua News Agency along with its history and reporting over the years, as the foundation for telling the story"--Provided by publisher